2021
DOI: 10.1016/j.jpsychires.2021.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm and the COVID-19 pandemic: A study of factors contributing to self-harm during lockdown restrictions

Abstract: Introduction The COVID-19 pandemic and resulting public health measures may have major impacts on mental health, including on self-harm. We have investigated what factors related to the pandemic influenced hospital presentations following self-harm during lockdown in England. Method Mental health clinicians assessing individuals aged 18 years and over presenting to hospitals in Oxford and Derby following self-harm during the period March 23rd to May 17, 2020 recorded wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 27 publications
6
52
0
Order By: Relevance
“…The findings are consistent with the notion that living arrangements are an important identifier of the differential risk of self-injury and domestic violence during a pandemic. Young adults living alone had an increased risk of self-injury; this is consistent with prior research on during-pandemic hospitalized individuals with self-injury who reported reduced opportunities for face-to-face contact with family members, friends, or partners, and a lack of social support (Hawton et al, 2021). Although we cannot tell from our data whether individuals who reported self-injury during the pandemic already felt isolated before the pandemic, our findings identify young people who live alone as an important target population for interventions during a pandemic and perhaps also in postpandemic times.…”
Section: Living Arrangementssupporting
confidence: 85%
“…The findings are consistent with the notion that living arrangements are an important identifier of the differential risk of self-injury and domestic violence during a pandemic. Young adults living alone had an increased risk of self-injury; this is consistent with prior research on during-pandemic hospitalized individuals with self-injury who reported reduced opportunities for face-to-face contact with family members, friends, or partners, and a lack of social support (Hawton et al, 2021). Although we cannot tell from our data whether individuals who reported self-injury during the pandemic already felt isolated before the pandemic, our findings identify young people who live alone as an important target population for interventions during a pandemic and perhaps also in postpandemic times.…”
Section: Living Arrangementssupporting
confidence: 85%
“…Most studies about entrapment and COVID-19 have dealt with suicides during COVID-19 [9,14], depression and anxiety [15], self-harm [16], and primarily report negative studies. However, Tesimann and Brailovkaia (2020) note said that suicide ideation is not an inevitable consequence of feelings of entrapment [17].…”
Section: Necessity Of the Studymentioning
confidence: 99%
“…Lockdown system or situation during the COVID-19 [3,6,18,26,29,[35][36][37][38][39][40][41], impairment to social and occupational functioning [9] Restricted situation Social consequences of COVID-19 [3], restrictions [35], physical distancing and self-isolation [36], isolation [29,42], reduced social opportunities [42], social restriction [38], isolation and loneliness/reduced contact with key individuals/ living alone/cessation or reduction of service (including absence of face to face support) [16], limited/restricted [43], social distancing [6,18,29,40,43], losing direct social and physical contact [9], restricted in a situation [44] Uncertain future…”
Section: Lockdown Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that emotional distress increases during pandemics ( 15 ). Furthermore, those being treated for existing mental health disorders may experience a worsening of their condition during pandemics ( 16 ). Additionally, undiagnosed mental health conditions could worsen during a pandemic and therefore become clinically relevant.…”
Section: Impact Of Covid-19mentioning
confidence: 99%